Playful approaches to news engagement. (June 2020) - Ferrer-Conill, Raul; Foxman, Maxwell; Jones, Janet; Sihvonen, Tanja; Siitonen, Marko
From crossword puzzles and quizzes to more complex gamification strategies and serious newsgames, legacy media has long explored ways to deploy playful approaches to deliver their content and engage with the audience. We examine how news and games fit together when news organizations, game creators and news audiences welcome gameful forms of communication and participation. Moreover, we reflect on the theoretical and empirical significance of merging news with games as a way to reformulate normative assumptions, production practices and consumption patterns. As a result, the boundaries between journalism and game's logics start to erode, and they begin to find new ways of converging.